The significance and determination by image analysis of microcrack density in hard chromium plating - Do Nascimento, Marcelino Pereira [UNESP]; Voorwald, Herman Jacobus Cornells [UNESP] (My University, 2008)
It is well known that the microcrack density is a fundamental parameter in hard chromium electroplating. The chemical and mechanical properties of this coating are widely dependent on its microcrack density. In this paper a simple image analysis procedure to determine microcrack density is presented in order to demonstrate it as a fundamental tool to estimate the fatigue, corrosion and wear behavior, as well as the residual stress field of a coated component. For this purpose, the image analysis procedure was carried out on two kinds of hard chromium plating - one called accelerated (high velocity of deposition and fluoride-free) and the other conventional (with fluoride). The coatings were applied on samples of AISI 4340 aeronautical steel, which is widely used in aircraft landing gear components. To characterize the practical significance of this study, the microcrack density results were related to the fatigue, wear and corrosion behavior from previous study and to the residual stress field in the coatings.
Keywords: Hard chromium electroplating; Image analysis; Microcrack density; Stereology; Surface coating